Performance Analysis of Biscuit Manufacturing Plant in Steady State Using Fuzzy Availability - Kumar, Pawan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper deals with the performance analysis of biscuit manufacturing plant consisting of six sub-systems using fuzzy availability in the steady state. These six sub-systems are arranged in series and parallel configurations. Mathematical formulation of the problem is carried out using Markov process and the governing differential equations are solved in steady state using normalizing condition. The effect of variations of fuzzy availability for different failure, repair rates and system coverage factor for each sub-system in steady state is also studied.